The Relevance of Istihsan to Contemporary Public Life: An Analysis of the Theory of Legal Change - Syarif Hidayatullah; Akhmad Mustangin; Alfitra Firmansyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Solving contemporary fiqh problems in Islamic law has many methods for studying them and finding laws to be applied by society. This research aims to determine the use of istihsan and its urgency in legal changes in contemporary society. This qualitative research uses a type of normative legal research, also called library legal research. The collection of legal materials used is a library study in the field of law, which from the perspective of binding strength can be divided into three groups, namely primary, secondary and tertiary legal materials. The study technique used is a combination of deductive and inductive. The deductive method is used to get a detailed picture from the general framework to specific explanations which are then drawn to a conclusion. The result of this research is that the application of law through istihsan is used for the benefit of the benefit. The basis for legal changes in istihsan is seen from several aspects: the existence of texts or special provisions, the existence of a special context, urf or customs, consideration of the benefit, or emergency.